LAW ENFORCEMENT AGAINST ILLEGAL FISHING IN NATUNA WATERS DURING THE COVID-19 PANDEMIC - Ida Kurnia (Fakultas Hukum Universitas Komputer Indonesia, 2021)
Law enforcement against illegal fishing in Natuna Waters during the Covid-19 pandemic is very important, especially considering frequent illegal fishing cases during the pandemic. Therefore, it is necessary to conduct an analysis of the efforts that have been made by the Indonesian Government to solve the illegal fishing cases that have occurred in Indonesia, regarding to the protection of fishermen, especially in Natuna Waters. The purpose of this study is to determine the role of the government regarding the form of law enforcement that have been carried out, utilizing various existing government policies and regulations, as well as the implementation of these regulations in the field, both in preventive, responsive and repressive efforts, in regards to illegal fishing cases in Natuna Waters. To study this, it is necessary to analyze various juridical reviews of the rights and obligations of the Indonesian State in Indonesian waters, data on the number of illegal fishing cases in Indonesia and in the Natuna region, and general analysis of illegal fishing cases. Furthermore, it should also include the type of facilities and infrastructure that must be strengthened. Using the method of normative legal analysis, we found several weaknessesin the legal norms.